Exploring News Coverage About Plant-Based Milk: A Content Analysis - Elise Regusci; Courtney Meyers; Nan Li; Erica Irlbeck (Journal of Applied Communications, 2022)
Plant-based milk has provided more options to consumers who are looking for an alternative to dairy milk. Recently, sales of plant-based milk have increased while dairy milk has continued to decline. To gather more insight into what is being discussed in news coverage about plant-based milk, a quantitative content analysis was conducted on 250 articles published from 2011 to 2020. These articles were coded for word count, location of publication, frame, and article type. The seven frames used to describe plant-based milk were Environment, Animal Welfare, Health, Economics, Labeling, Taste, and Trend. There was an increase in articles published each year, with the most articles published in 2019. The Trend frame was the most popular frame followed by Taste and Health. The Trend frame is related to the growing popularity of plant-based milk. Many Taste articles were written in the form of recipes, which gives inspiration to the reader to use plant-based milk while cooking or baking. The use of the Health frame focused on nutritional information and support of using plant-based milk as an alternative for lactose intolerance or milk allergy. Overall, this study indicated that most plant-based milk news coverage focuses on discussing popularity, consumption, and innovation about plant-based milk. Recommendations for future research and practice are provided.
Keywords: content analysis; framing; frames; plant-based milk; news